At the brink of supercoloniality: genetic, behavioral, and chemical assessments of population structure of the desert ant Cataglyphis niger - Saar, Maya; Leniaud, Laurianne; Aron, Serge; Hefetz, Abraham (Frontiers in Ecology and Evolution, 2014)
The nesting habits of ants play an important role in structuring ant populations. They vary from monodomy, a colony occupies a single nest, via polydomy, a colony occupies multiple adjacent nests, to supercoloniality, a colony spans over large territories comprising dozen to thousands nests without having any boundaries. The population structure of the desert ant Cataglyphis niger, previously considered to form supercolonies, was studied using genetic, chemical and behavioral tools in plots of 50x50 meters at two distinct populations. At the Palmahim site, the plot comprised 15 nests that according to the genetic analysis constituted three colonies. Likewise at the Rishon Leziyyon site 14 nests constituted 5 genetic colonies. In both sites, both chemical analysis and the behavioral (aggression) tests confirmed the colony genetic architecture. The behavioral tests also revealed that aggression between colonies within a population was higher than that exhibited between colonies of different populations, suggesting the occurrence of the “nasty neighbor” phenomenon. In contrast to supercolony structure previously reported in another population of this species, the presently studied populations were composed of polydomous colonies. However, both the genetic and chemical data revealed that the inter-colonial differences between sites were larger than those within site, suggesting some within-site population viscosity. Thus, C. niger exhibits flexible nesting characteristics, from polydomy to supercoloniality, and can be considered at the brink of supercoloniality. We attribute the differences in population structure among sites to the intensity of intraspecific competition.